Inorganic-organic hybrid materials based on functionalized silica and carbon: a comprehensive understanding toward the structural property and catalytic activity difference over mesoporous silica and carbon supports - Bordoloi, Ankur; Mathew, Nevin T.; Lefebvre, F.; Halligudi, Shivaraj B. (Microporous and Mesoporous Materials, 2008)
Inorganic-organic hybrid materials based on functionalized silica and carbon were synthesized by anchoring molybdovanadophosphoric acid (H-5[PMo10V2O40]center dot 32.5H(2)O) onto amine-functionalized SBA-15, ethane-bridged SBA-15 and mesoporous carbon, respectively. Small angle X-ray diffraction, N-2 sorption analysis, HRTEM, SEM, IFT-IR, CP-MAS NMR were used to diagnose the mesoporous structure of inorganic-organic hybrid materials. The structural integrity of molybdovanadophosphoric acid has been found to be retained after immobilization over mesoporous materials. These inorganic-organic hybrid materials were tested in the environmentally friendly oxidation of 2-methylnaphthalene (2MN) with 30%, aqueous hydrogen peroxide. Molybdovanadophosphoric acid containing mesoporous organosilica hybrid material (ethane-bridged SBA-15) exhibited higher catalytic activities in the oxidation of 2MN to give a clean product 2-methy-1,4-naphthoquinone (menadione vitamin K3 precursor), because of the improved hydrophobicity of the material. The correlation between structural properties and catalytic activities of these hybrid materials has been well addressed in our present studies. (c) 2008 Elsevier Inc. All rights reserved.
Keywords: 2-Methylnaphthalene; inorganic-organic hybrid materials; mesoporous carbon; mesoporous organosilica; Oxidation